THE OPTIMAL CROP ROTATION OF AI-RASHEED DISTRICT FARMS USING LINEAR PROGRAMMING TECHNIQUE - Al-Nassr, R. Sh. M. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
The objectives of this research are to determine the optimal agricultural plane to achieve the optimum crop combination that maximizes the profits and the total and net agricultural income of the Al-Rasheed / Hamorabi Farm in Baghdad using L.P technique to reach the production volume that maximizes profit to choose the best plan and to increase the efficiency of the use of available resources at the farm level, to optimize the utilization of natural water resources and to protect them from the risk of attrition and to promote their use by deriving mathematical models for use in water needs assessment, including the application of an agricultural rotation to maintain soil fertility. The research has reached a number of conclusions, perhaps the most important is that the optimal solution using the linear programming method shows us the difference in the optimum crop combination of the actual crop structure of the agricultural crops and their areas. The farm has achieved a much higher income than the resulting income of the actual farm plan, as explained by the resource-based model, the LHS of the model, is less than the available resources that represent the RHS, which means that optimal plans have used fewer resources and given higher net income. From the conclusions reached, we can make a number of recommendations. The most important of these is the implementation of the linear programming technique to determine the extent to which the available resources are invested efficiently, which helps to increase the production in order to achieve the economic efficiency of the farmers and the need to generalize and apply this method in associations with similar environments to determine the optimal use of different productive resources.